Esmolol and Lidocaine in Blunting Hemodynamic Response to Extubation - Dangol, Shova; Yadav, Rajesh Kumar; Bhatt, Prashant (Journal of College of Medical Sciences-Nepal, 2025)
Background Tracheal extubation is one of the routinely performed procedures in the practice of anaesthesiology. It has been reported that it increases heart rate and blood pressure by 15-30% lasting for 5 to 15 minutes. Incidence of increase in HR and BP is four times more during extubation in comparison to intubation. Various pharmacological interventions have been tried to attenuate these hemodynamic responses as Lidocaine, Propofol, Esmolol or opioids. Objective of this study is to evaluate and compare the efficacy of Esmolol and Lidocaine in blunting hemodynamic response to extubation. Methods This was a comparatove study performed in 70 patients of ASA grade I and II. Patients were divided into Esmolol group and Lidocaine group. Data were collected and Statistical analysis was done using independent t-test to compare means for continuous variable like age, weight, heart rate, SBP, DBP and MBP. Chi-square test was used to test difference in proportion of categorical outcomes in different drug groups. Results There was significant increase in heart rate at the time of extubation and at 1 min after extubation in-group L compared to group E (p-value<0.005). SBP was also found significantly increased at the time of extubation and 3 min after extubation in group L as compared to group E (p-value<0.05). Conclusions Esmolol 1.5mg/kg given 3 minutes before extubation is better than Lidocaine 1.5mg/kg in attenuating hemodynamic responses to extubation.